The tale of Tillie's dragon - Welker, Frank; Soucie, Kath.; Kassir, John.; Taylor, Russi; Stribling, Mike.; Nago, Isao.; Children's Treasury Entertainment (Firm); Stribling Entertainment (Firm); Monarch Home Video (Firm); Bridgestone Multimedia Group ([S.l.] : Stribling Productions : Distributed by Monarch Home Video, 1999)
Tillie finds the adventure of a life time with her new friend Herman, the dragon.
At head of cassette label title: Monarch Home Video presents.
Videocassetter release of the c1995 production.
"A Children's Treasury classic"--Container.
"Bridgestone Multimedia Group"--Container.
Animation, S.H. Productions ; original music score, Chase/ Rucker Productions.
Voices of Kath Soucie, John Kassir, Wayne Powers, Frank Welker, Randy Rudy, Russi Taylor ; narrator: Frank Welker.
Keywords: Dragons -- Juvenile fiction; Animated films; Feature films